Pemberlakuan Pajak terhadap Barang Hasil Transaksi Jasa Titip Online - Ahmad, Usamah Rievzqy (Jurnal Suara Hukum, 2020)
As time goes by, technologies are developing more and more. One of a result of it that we know is internet. Internet is a network that enable to connect every human being in all over the world. Internet gave us many positive impacts, to fulfil our daily needs is one of them. Thanks to internet we can do our business activities more effective. One of the business activites that we can do is vending, selling things by internet known as online shopping. Many people can sell anything through online shopping such as goods and services. They called â€œJasa Titip Onlineâ€, is one type of a business that let consumer told us what they want to and then we look and buy goods that consumers want. â€œJasa Titip Onlineâ€ devided into two kinds, first is domestic purchases and the second is overseas purchases. Problems arise from the overseas purchases, person who conduct â€œJasa Titip Onlineâ€ must collect things from other country then bring it to Indonesia. That will create new competitors for large companies involved in the export-import business. Goods that sold by export-import companies supposed to be taxed when entering Indonesian territory. However same things didnâ€™t happen to a person who commit â€œJasa Titip Onlineâ€, it should be taxed to create fair business competition. The tax provisions currently in force are stated in Peraturan Menteri Keuangan No. 203 Tahun 2017 that define imported goods brought by a person for personal purposes that worth under US$ 500 will be free on board. That provisions are less effective due to more people conduct â€œJasa Titip Onlineâ€ that somehow brought things more than US$ 500 but still free on board.